2023
DOI: 10.7759/cureus.49204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approach to Post-acute Sequelae After COVID-19 Infection and Vaccination

Nicolas Hulscher,
Brian C Procter,
Cade Wynn
et al.

Abstract: The spike protein of SARS-CoV-2 has been found to exhibit pathogenic characteristics and be a possible cause of post-acute sequelae after SARS-CoV-2 infection or COVID-19 vaccination. COVID-19 vaccines utilize a modified, stabilized prefusion spike protein that may share similar toxic effects with its viral counterpart. The aim of this study is to investigate possible mechanisms of harm to biological systems from SARS-CoV-2 spike protein and vaccine-encoded spike protein and to propose possible mitigation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Specific types of PACS can be defined based on the presentation of symptoms [278,279]. Not surprisingly, because of the common denominator between infection and mRNA inoculation (the S-protein), COVID-19 vaccination produces long-term symptoms that share many features with PACS [280,281]. The condition may be triggered by an immune overreaction to the vaccine-generated S-protein [282], which has been shown to persist at least six months after the injection [283].…”
Section: Discussionmentioning
confidence: 99%
“…Specific types of PACS can be defined based on the presentation of symptoms [278,279]. Not surprisingly, because of the common denominator between infection and mRNA inoculation (the S-protein), COVID-19 vaccination produces long-term symptoms that share many features with PACS [280,281]. The condition may be triggered by an immune overreaction to the vaccine-generated S-protein [282], which has been shown to persist at least six months after the injection [283].…”
Section: Discussionmentioning
confidence: 99%
“…Hulscher et al found that COVID-19 vaccine-induced myocarditis can most likely result in sudden cardiac death using post-mortem analysis in 28 autopsy cases [20]. COVID-19 mRNA vaccines systemically distribute mRNA via LNPs that encodes for the Spike protein, which has been shown to incite deleterious effects in multiple organ systems and cause fibrinolysis-resistant blood clots [25,26]. Baumeier et al found Spike protein and no nucleocapsid in the myocardium of 15 individuals with COVID-19 vaccine-induced myocarditis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although nattokinase preparations are widely available commercially, and as noted above they are considered to have significant therapeutic value, including in Long COVID [256,257], their exact contents are uncertain, and so we decided that it was best to create and use purified, recombinant material.…”
Section: (And Healthmentioning
confidence: 99%